The impact of the EU Industrial R&D Investment Scoreboard in science and policy - Hugo Confraria; Nicola Grassano; Pietro Moncada Paternò Castello; Elisabeth Nindl (European Commission, Joint Research Centre (JRC), 2024)
Understanding the flow of knowledge between scientific research and policymaking is increasingly important. This study examines the influence of the EU Industrial R&D Investment Scoreboard, a monitoring report produced for policy makers, researchers, and businesses since 2004. We analyse citation trends in scientific publications and policy documents to assess the S reach and impact. Our findings indicate that the Scoreboard is cited more frequently in policy documents, though academic interest is growing. Policy documents cite the Scoreboard more quickly, reflecting its immediate relevance, while scientific publications take longer to cite it and utilise its data. Papers citing the Scoreboard tend to have a higher citation impact than average, and appear in a wide range of disciplines and journals. In our citation content analysis, we find that "insight" citations are more common than "data" citations. However, publications combining patent and Scoreboard data tend to receive more citations, highlighting the value of integrating R&D data with other relevant variables to better understand the innovation process. Finally, we show how the Scoreboard has influenced EU policy discourse to address the need for structural changes towards high R&D intensity sectors, and showing EU's leadership in green innovation.
Keywords: 330